Ne znam ni gde, ni kad, ni kako . I Don't Know Where, Or When, Or How - Gvardiol, Zelimir (Yugoslavia, 1995)
Since 1986 the death rate among older people in Yugoslavia has risen five times and the number of suicides has increased dramatically. The film captures a sensitive portrait of a number of aged people in the war-torn country, their alienation, confusion and, most importantly, their sense of dignity.